(untitled) (Journal of Applied Oral Science, 2005)
The tissue response to porous bovine anorganic bone implanted in rat connective tissue was evaluated by subjective light microscopy analysis. Forty rats were divided into two groups: control (empty collagen capsules) and test (collagen capsule filled with 0.1g biomaterial) and killed 10, 20, 30 and 60 days after implantation. At 10 days, intense chronic inflammatory infiltrate consisting mainly of macrophages and inflammatory multinucleated giant cells (IMGC) was observed. Neutrophils, plasma cells and lymphocytes were present in discrete amounts and slowly disappeared along the repair process. Porosity of the material was filled by reaction connective tissue exhibiting IMGC. The fibrosis was more intense after 60 days and clearly higher than the control group. Thus, the material did not cause any severe adverse reactions and did not stimulate the immune system. Based on the results it could be concluded that deproteinized bovine cancelous bone was well tolerated by rat connective tissue.